Speech and Language Development in ADHD - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1999)
Speech discrimination and phonological working memory were examined in children with ADHD (N=9), ADHD plus developmental coordination disorder (ADHD+DCD) (N=13), and 19 age-matched controls, in a study at the Neuropediatric Unit, Karolinska Institute, Stockholm, Sweden.